New Gramscian paths - Liguori, Guido (Marx, Engels, and Marxisms., 2026)
Guido Liguori's book Nuovi sentieri gramsciani is at the cutting edge of Gramscian scholarship. Now available in English, this generous book offers a plenitude: biographical, philological, and interpretative advancements in Antonio Gramsci's political thought to provide new perspectives on key moments in his life and thought.Grounded in a deep and attentive reading of Gramsci's works focusing on his pre-prison years, Liguori historically reconstructs and contextualises Gramsci's ideas within the broader political, social, ideological, and philosophical landscape of his time. This includes Gramsci's engagement with the Russian Revolution, the "Red Biennium" 1919-1920, the foundation of the Communist Party in Italy, his stay in Moscow in the years of the "New Economic Policy" and his meeting with Lenin; and some of the main aspects of his elaboration (the "Southern Question" in Italy, the interpretation of Machiavelli, and the theme of autonomy of politics within Marxist theory, the concept of "subaltern").Guido Liguori's writing style is both accessible and rigorous making New Gramscian Paths suitable not only for specialists but also for a broader audience interested in Gramsci.